"I just want to count them! Considerations when choosing a deer population monitoring method". Issue 6 (1st December 2014) - Amos, Matt; Baxter, Greg; Finch, Neal; Lisle, Allan; Murray, Peter
Abstract : Effective management of any population involves decisions based on the levels of abundance at particular points in time. Hence the choice of an appropriate method to estimate abundance is critical. Deer are not native to Australia and are a declared pest in some states where their numbers must be controlled in environmentally sensitive areas. The aim of this research was to help Australian land managers choose between widely used methods to count deer. We compared population estimates or indices from: distance sampling, aerial surveys, spotlight counts, and faecal pellet counts. For each we estimated the labour input, cost, and precision. The coefficient of variation varied with method and time of year from 8.7 to 36.6%. Total labour input per sampling event varied from 11 to 136 h. Total costs of vehicles and equipment per sampling event varied from AU913 to 2966. Overall, the spotlight method performed the best at our study site when comparing labour input, total cost and precision. However, choice of the most precise, cost effective method will be site specific and rely on information collected from a pilot study, We provide recommendations to help land managers choose between possible methods in various circumstances.